Ergogenic Effects of 8 Days of Sceletium Tortuosum Supplementation on Mood, Visual Tracking, and Reaction in Recreationally Trained Men and Women. Issue 9 (September 2020) - Hoffman, Jay R.; Markus, Irit; Dubnov-Raz, Gal; Gepner, Yftach
Abstract : Abstract: Hoffman, JR, Marcus, I, Dubnov-Raz, G, and Gepner, Y. Ergogenic effects of 8 days of Sceletium tortuosum supplementation on mood, visual tracking, and reaction in recreationally trained men and women. J Strength Cond Res 34(9): 2476–2481, 2020— Sceletium tortuosum (ST) is a South African plant that has been reported to promote a sense of well-being in healthy individuals and used in treating people with anxiety, stress, or depression. These studies have been conducted in middle-aged and older adults, but no investigations have been performed in a healthy, young adult population. Thus, the purpose of this study was to examine the effect of 8 days of ST extract (25-mg) supplementation on changes in reactive agility, visual tracking, and mood. Sixty recreationally trained men ( n = 48) and women ( n = 12), between 20 and 35 years, were randomly assigned to 1 of 2 groups: ST or placebo (PL). Subjects were tested on 2 occasions: before supplementation and 2-hours after supplementation on day 8. Subjects completed a subjective questionnaire to assess alertness and energy using a visual analog scale (VAS). In addition, subjects completed the Profile of Mood States questionnaire and performed reactive agility and visual tracking assessments. Significant improvements were noted for ST in complex reactive performance that required subjects to respond to repeated visual stimuli with a cognitive load compared with PL. However, no significant changes were noted between the groups in either VAS or total mood score. In addition, no differences were observed in simple reaction assessments. The results of this study demonstrate an ergogenic benefit in complex reactive tasks that include a cognitive load. However, in this subject population studied, no benefits in mood were observed.